The Role of Networks in SMEs in Supporting Internationalization: Literature Study - Vembri Aulia Rahmi; Sudarmiatin Sudarmiatin; Hadi Sumarsono (Cita Konsultindo Research Center, 2023)
The role of SMEs as the engine of the economy with all its problems is still a concern because of the contribution of sales to the overall economy. The weakness of SMEs, especially from the element of resources, results in limitations in developing the business. However, business continuity in SMEs directs companies to make business improvements, through internationalization. Meanwhile, the knowledge and skills needed by SMEs for internationalization are inadequate. Therefore, SMEs need to build a network that not only helps meet the weaknesses of UKM's resources, but can provide information and knowledge that supports internationalization. Thus, this paper is intended to provide insight into the role of networks in directing SMEs towards internationalization. The qualitative approach in this research is to use the literature study method. The results of studies from several studies on SMEs in several regions of the world explain several things regarding